An era of conflicting commitments: Portugal’s force planning during the cold war - Rocha, J. S. (National armies and NATO, 1949-1991: The burden of alliance, 2025)
At different times during the four decades of the Cold War, Portugal, a founding member of NATO, faced major challenges in creating, developing, and sustaining a military apparatus that would simultaneously guarantee the military defence of its homeland and overseas territories, as well as having the means to fulfil the defence agreements signed both with Spain for the joint defence of the Iberian Peninsula in the Pyrenees and with NATO for the defence of Western Europe. This chapter describes the context in which Portuguese defence planners had to consider different ground force deployment scenarios and explains the domestic and external constraints that influenced force planning from 1950 to 1991. Keywords: Portugal, Force Planning, NATO, Cold War, Spain, Africa